2020
DOI: 10.2217/bmm-2019-0291
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Plasma Free Fatty Acid Level for Assessing and Diagnosing Acute Myocardial Infarction

Abstract: Aim: To clarify the diagnostic value of the circulating free fatty acid (FFA) level for acute myocardial infarction (AMI) in coronary heart disease patients. Methods & results: A total of 1776 patients were screened by coronary angiography from October 2014 to February 2016. The plasma FFA level was significantly higher in coronary heart disease patients with lesions in three or more vessels than those with lesions in one or two vessels. Moreover, an elevated FFA level was identified as an indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…However, this study did not use quantitative tools to stratify ACS risk, which requires further research and exploration in the future. In terms of the diagnostic value of FFA, Kan et al recently drew the ROC curve of FFAs for the diagnosis of AMI and found that its AUC was 0.77 in men and 0.80 in women, which was greater than hsCRP and ProBNP [27]. Our study expanded the application of FFAs to ACS patients and found that it is equally feasible in assisting the diagnosis of ACS in patients with pCAD.…”
Section: Discussionmentioning
confidence: 70%
“…However, this study did not use quantitative tools to stratify ACS risk, which requires further research and exploration in the future. In terms of the diagnostic value of FFA, Kan et al recently drew the ROC curve of FFAs for the diagnosis of AMI and found that its AUC was 0.77 in men and 0.80 in women, which was greater than hsCRP and ProBNP [27]. Our study expanded the application of FFAs to ACS patients and found that it is equally feasible in assisting the diagnosis of ACS in patients with pCAD.…”
Section: Discussionmentioning
confidence: 70%
“…Ying et al 3 found that the change of plasma FFA level after AMI was more signi cant in women than men. The relationship between FFA and ischemic heart disease is clear, but the role of predictive risk in patients with AMI is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Clinical symptoms of myocardial ischemia; (2) The electrocardiogram showed new myocardial ischemia changes and new ST-segment elevation changes of the left bundle branch block. (3) Pathological Q wave appeared in Electrocardiograph (ECG).…”
Section: Eligibility Criteria {10}mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, an increasing number of studies has confirmed the association between FFA and heart disease, and serum FFA has been concomitant to an augmented risk of coronary heart disease. High FFA levels reflect the severity of myocardial ischemia and necrosis[ 16 ].…”
Section: Introductionmentioning
confidence: 99%